Controllable Liquid-Liquid Printing with Defect-free, Corrosion-Resistance, Unrestricted Wetting Condition - Min, Lingli; Zhang, Haohui; Pan, Hong; Wu, Feng; Hu, Yuhang; Sheng, Zhizhi; Wang, Miao; Zhang, Mengchuang; Wang, Shuli; Chen, Xinyu; Hou, Xu (iScience, 2019)
Conventional printing is worth revisiting because of its established procedures in meeting the surging demand of manufacturing printed electronics, 3D products, etc. However, one goal in penetrating printing into these is to control pattern transfer with no limitation of wettability. Here we introduce a miscible liquid-liquid transfer printing mechanism that can synchronize material preparation and material patterning with desirable properties including limitless selection of raw materials, corrosion resistance, no wetting constraint, and ability to prepare large-area defect-free materials for multi-function applications. Theoretical modeling and experiments demonstrate that donor liquid could be used to make patterns within the bulk of a receiver material, allowing the obtained intrinsically patterned functional materials to be resistant to harsh conditions. Different from current liquid printing technologies, this printing approach enables stable and defect-free material preparation and is expected to prove useful in flexible display, soft electronics, 4D printing, and beyond. [Display omitted] •A transfer printing mechanism based on miscible liquid-liquid interfaces•The material preparation and defect-free patterning can be synchronized•This printing mechanism is free of wetting constraint Interface Science; Surface Property; Materials Property; Materials Design